2014
DOI: 10.22146/ijc.21233
|View full text |Cite
|
Sign up to set email alerts
|

Production of Reducing Sugar from Cassava Solid Waste by Simultaneous Ultrasonication and Acid Hydrolysis

Abstract: In this study, acid hydrolysis of cassava solid waste under ultrasound irradiation for reducing sugar production was studied. A series of experiments was carried out under a 40 kHz ultrasound irradiation, with the main purpose to examine the effect of pHs, hydrolysis times, and temperatures on the concentration of reducing sugar produced. As a control an untreated sample was subjected to thermal hydrolysis under the optimum condition obtained from the hydrolysis experiments under ultrasound treatment. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Only a few reports regarding the production of reducing sugar from cassava or taro can be found in the literature. Simanjuntak et al reported the production from cassava solid waste by simultaneous ultrasonication and acid hydrolysis. Their best result was 0.8 g L −1 of reducing sugar (using 40 kHz ultrasound irradiation, pH = 2.0, 90 min of hydrolysis time, and 90 °C).…”
Section: Resultsmentioning
confidence: 99%
“…Only a few reports regarding the production of reducing sugar from cassava or taro can be found in the literature. Simanjuntak et al reported the production from cassava solid waste by simultaneous ultrasonication and acid hydrolysis. Their best result was 0.8 g L −1 of reducing sugar (using 40 kHz ultrasound irradiation, pH = 2.0, 90 min of hydrolysis time, and 90 °C).…”
Section: Resultsmentioning
confidence: 99%
“…HMT exerted significant effects on starch characteristics in cassava; the process decreased total starch content, and then increased reducing sugar and amylose content. Simanjuntak et al [25] showed that reducing sugars were increased during heating. Starch (polysaccharide), which is mainly composed of glucose (monosaccharide), was degraded at higher temperatures [26].…”
Section: Discussionmentioning
confidence: 99%
“…Simanjuntak et al . [ 25 ] showed that reducing sugars were increased during heating. Starch (polysaccharide), which is mainly composed of glucose (monosaccharide), was degraded at higher temperatures [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liquid fuels produced were then evaluated using gas chromatography-mass spectrometry (GC-MS), providing the information on the chemical content of the liquids, enabling the comparison of the performance of the zeolites synthesized to be made. The use of cassava solid waste is based on the availability of this agricultural waste in Indonesia, however, the utilization of this feedstock for renewable energy such as bioethanol production is still limited [23][24][25][26][27]. Water hyacinth is an aquatic plant that can be found in various water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…From environmental point of view, water hyacinth is considered a very problematic plant [19,20] because of the various problems it causes to the water ecosystem and the use of water for other purposes, such as transportation. From the biomass perspective, on the other hand, this plant is a very potent source for its fast-growing with high mass productivity, making it an interesting raw material for biomass utilization, such as production of renewable energy sources using pyrolysis [21][22][23]. In this study, a series of trials was operated with the purposes to investigate the effect of crystallization times on the formation of HS, to compare the compositions of the liquid fuels produced using the HS produced with different crystallization times, and to compare the compositions of the liquid fuels obtained from different raw materials pyrolyzed.…”
Section: Introductionmentioning
confidence: 99%